Overheating in Small Euro Area Economies Should Fiscal Policy React? - Hoeller, Peter (OECD Economics Department Working Papers, 2002)
This paper reviews first the fiscal policy recommendations by the EU, the IMF and the OECD for Finland, Greece, Ireland, Luxembourg, the Netherlands, Portugal and Spain. All these countries had inflation above the euro area average in early 2001, some by a considerable margin. The fiscal policy prescriptions deviate little, the EU, the IMF and the OECD generally recommending an active use of fiscal policy. There are some exceptions, however. The next section examines indicators of excess demand in these countries. This is followed by a review of the factors that help or hinder market-based adjustment, including simulations to gauge their effect. Market-based adjustment to demand shocks depends critically on whether the effect of a lower real interest rate is strong relative to the loss in competitiveness, on the size of wealth effects, on wage and price setting behavior, on the supply response and on the strength of trade integration. Simulations suggest that market-based ...